Antioxidant cascades confer neuroprotection in ethanol, morphine, and methamphetamine preconditioning. (December 2019) - Lu, Shuang; Liao, Lvshuang; Zhang, Bing; Yan, Weitao; Chen, Liangpei; Yan, He; Guo, Limin; Lu, Shanshan; Xiong, Kun; Yan, Jie
Highlights: Preconditioning confers protective effects in many tissues including the brain. Ethanol (EtOH), morphine, and methamphetamine (METH) are neurotoxic. Low doses of EtOH, morphine, and METH have neuroprotective effects. EtOH, morphine, and METH preconditioning involves antioxidant mechanisms.